Changes in Quality of Life Following SARS-CoV-2 Infection Among Jewish and Arab Populations in Israel: A Cross-Sectional Study - Jelte Elsinga; Jelte Elsinga; Paul Kuodi; Haneen Shibli; Yanay Gorelik; Hiba Zayyad; Hiba Zayyad; Ofir Wertheim; Kamal Abu Jabal; Kamal Abu Jabal; Amiel Dror; Amiel Dror; et al. (Frontiers Media S.A., 2023)
Objectives: The long-term impact of COVID-19 on health inequalities is under-researched. We investigated changes in health-related inequalities following SARS-CoV-2 infection between the Jewish majority and the Arab/Druze minority in Israel.Methods: Patients with a positive SARS-CoV-2 RT-PCR test processed from one of the Northern-Israeli government hospitals between 03/2021 and 05/2022 were invited to participate. We collected socio-demographic, COVID-19-related, and health-related quality of life (HRQoL) information using a validated questionnaire. We compared pre- and post COVID-19 HRQoL changes between Jews and Arabs/Druze, up to 12+ months post-infection using an adjusted linear regression model.Results: Among the 881 included participants the average post-COVID HRQoL score was lower among Arabs/Druze than Jews (0.83 vs. 0.88; p = 0.005). Until 12 months post-infection, HRQoL changes were similar for Arabs/Druze and Jews. After 12 months, HRQoL dropped significantly more among Arabs/Druze than among Jews (0.11 points difference between the groups; p = 0.014), despite adjusting for socioeconomic variables.Conclusion: 12 months post-infection, COVID-19 affected the HRQoL of Arabs/Druze more than Jews, with the gap not fully explained by socio-economic differences. The COVID-19 pandemic may widen pre-existing long-term health inequalities.